Dental prophylaxis decreases the risk of acute myocardial infarction: a nationwide population-based study in Taiwan - Lee YL (Dove Medical Press, 2015)
Ya-Ling Lee,1,2 Hsiao-Yun Hu,2,3 Pesus Chou,2 Dachen Chu2,4,5 1Department of Dentistry, Taipei City Hospital, 2Institute of Public Health and Community Medicine Research Center, National Yang-Ming University, 3Department of Education and Research, Taipei City Hospital, 4Department of Health Care Management, National Taipei University of Nursing and Health Sciences, 5Department of Neurosurgery, Taipei City Hospital, Taipei, Taiwan Purpose: To investigate the association between periodontal disease (PD) and acute myocardial infarction (AMI), and evaluate the effect of dental prophylaxis on the incidence rate (IR) of AMI.Methods: The Longitudinal Health Insurance Database 2000 from the National Health Insurance program was used to identify 511,630 patients with PD and 208,713 without PD during 2000–2010. Subjects with PD were grouped according to treatment (dental prophylaxis, intensive treatment, and PD without treatment). The IRs of AMI during the 10-year follow-up period were compared among groups. Cox regression analysis adjusted for age, sex, socioeconomic status, residential urbanicity, and comorbidities was used to evaluate the effect of PD treatment on the incidence of AMI.Results: The IR of AMI among subjects without PD was 0.19%/year. Among those with PD, the IR of AMI was lowest in the dental prophylaxis group (0.11%/year), followed by the intensive treatment (0.28%/year) and PD without treatment (0.31%/year; P<0.001) groups. Cox regression showed that the hazard ratio (HR) for AMI was significantly lower in the dental prophylaxis group (HR =0.90, 95% confidence interval =0.86–0.95) and higher in the intensive treatment (HR =1.09, 95% confidence interval =1.03–1.15) and PD without treatment (HR =1.23, 95% confidence interval =1.13–1.35) groups than in subjects without PD.Conclusion: PD is associated with a higher risk of AMI, which can be reduced by dental prophylaxis to maintain periodontal health. Keywords: periodontal disease, acute myocardial infarction, dental prophylaxis, dental scaling